2020
DOI: 10.1088/1757-899x/870/1/012025
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Concentrations of Nitrite and Nitrate of Tigris River Water in Baghdad and Their Suitability to the Conditions Permitted Internationally

Abstract: Water is the most important natural resources in countries with desert and semi-desert climates like Iraq because it controls the distribution of population and economic activities, especially agriculture. Water pollution is one of the major global problems of the scientific and political community. It threatens health, threatens life, impairs industrial activity and develops civilization. So this work aims to determine the qualitative changes in Tigris River water in Baghdad city through the evaluation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…These processes are used in wastewater treatment plants to eliminate nitrogenous pollutants, turning nitrates into nitrogen, this is done through the aeration basins (aerobic biological processes) in the wastewater treatment plant, which is bacterial, as nitrogen is the DNA of proteins, amino acids, some fats, and others. If eaten in moderation, nitrates may not be harmful to an individual's health but may be a problem for young children and those with abnormal gut microbiomes [20]. Figure 4 shows that the value of nitrate was within the permissible range of (3.28 mg/l -6.4 mg/l) according to the Iraqi Rivers Conservation System No.…”
Section: Results Of Nitrate (No3) Valuesmentioning
confidence: 97%
See 2 more Smart Citations
“…These processes are used in wastewater treatment plants to eliminate nitrogenous pollutants, turning nitrates into nitrogen, this is done through the aeration basins (aerobic biological processes) in the wastewater treatment plant, which is bacterial, as nitrogen is the DNA of proteins, amino acids, some fats, and others. If eaten in moderation, nitrates may not be harmful to an individual's health but may be a problem for young children and those with abnormal gut microbiomes [20]. Figure 4 shows that the value of nitrate was within the permissible range of (3.28 mg/l -6.4 mg/l) according to the Iraqi Rivers Conservation System No.…”
Section: Results Of Nitrate (No3) Valuesmentioning
confidence: 97%
“…The average total hardness of the Tigris River in the Baghdad region was (253.6 mg/l -394 mg/l) total water hardness in Baghdad is within the permitted range of the World Health Organization (500 mg/l). Moreover, the detection strategy based on the slightly discussed selfcalibration technique improves the detection accuracy significantly [20]. However, hardness is not the appropriate criterion for irrigation water as calcium and magnesium are useful ions in the soil.…”
Section: Results Of Total Hardness (Th) Valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though emerging technology will exacerbate problems, opportunities have arisen to implement innovative solutions in the direction of more intelligent and virtual reality applications of building design. We are replacing conventional physical places with digital ones that could be accessed through smart devices as we gradually operate from a remote space, upgrading as well as learning skills online, and purchasing what we need from websites 22,23,18,19,20,31,41,54 . Increasing reliance on the internet media in building design, taking account of its effect on lifestyle, could continue after the COVID-19 outbreak, affecting all aspects of design and urban planning.…”
Section: Intelligent Buildings In the Light Of The Covid-19 Outbreakmentioning
confidence: 99%
“…Unfortunately, studies have shown that most of the water treatment plants (WTPs) are insufficient and cannot eliminate many of these contaminants (Ali and Jain, 1998, Ali and Aboul-Enein, 2002, Ali et al, 2005, Basheer and Ali, 2018, Ali et al, 2019. Most consumers dispose of their unused and expired prescriptions by throwing them in the toilet, sink, or trash sink (Gaffney et al, 2014, Rzaij et al, 2020.…”
Section: Introductionmentioning
confidence: 99%